Mobbing or workplace harassment; review of the issue in Colombia - Carvajal Orozco, José Gabriel; Dávila Londoño, Carlos A. (Cuadernos de Administración, 2013)
Mobbing is recognized as a promising line of work and high impact on man, organizations, and society. In Latin America, and specifically in Colombia, little development has been identified on the topic; this is a potential weakness against to the possibilities of knowing and intervening against it, which is accepted as a growing reality throughout the world. The objective of this paper is to present the results of the review and analysis of the issue of mobbing for Colombia. The document is divided into four parts. The first summarizes the main theoretical elements of the discussion about mobbing. In the second, we review mobbing legislation in Colombia. The third part presents an analysis of the work done by academic communities in the country on the subject. Finally, we portray the little development on topic in Colombia, the predominance of theoretical works, and from different areas than administrative. It has also been found that the heterogeneity and the low number of jobs make comparisons difficult; however, they share a similar conceptual, empirical, and legal framework.